Respiratory tract infection: Current pattern of pathogens involved and related antibiotic resistance observed at a tertiary health care institute of Rajasthan - Mathur, Navgeet; Verma, Yadav Narayan; Mathur, Medha (Indian Journal of Community Health, 2025)
Background: Antibiotic resistance is one of the contributing factors responsible for increased morbidity and mortality. Objectives: The study was designed to assess the current pattern of involved pathogens in respiratory tract infections with relevant antibiotic sensitivity and resistance to improve patient outcomes. Methodology: The study was conducted for 6 months and positive cultured sample reports of respiratory secretions in the form of sputum, tracheal secretion, bronchial aspirate, and pus were included in the study. Pathogens involved and antibiotic sensitivity, resistance were observed for respiratory secretion and pus separately. Results: A total 129 samples including 83 respiratory secretion samples and 46 pus samples cultures were found positive for organisms and included in the study. Among respiratory secretion cultures, Pseudomonas were most common organism (60%) followed by E. Coli, Klebsiella, Acinetobacter, Staphylococcus aureus, Citrobector, and Candida. Among pus cultures, Staphylococcus was the most common organism (23.90%) followed by E.Coli, Klebsiella, Pseudomonas, Citrobactor, Coagulase negative staphylococcus, Proteus. These pathogens were resistant to many first-line antibiotics. Conclusion: Antibiotic resistance to first-line antibiotics has emerged as alarming situation and contributes to morbidity and mortality. The current pattern of involved pathogen and antibiogram may help to decide appropriate empirical treatment.